2018
DOI: 10.1017/qua.2018.1
|View full text |Cite
|
Sign up to set email alerts
|

Glacial–interglacial change in chlorite concentration from the Lingtai section in the Chinese Loess Plateau over the past 1.2 Ma and its possible forcing mechanisms

Abstract: High-precision concentrations of chlorite minerals from the Lingtai section in the Chinese Loess Plateau and the surrounding deserts are presented through a mineral liberation analyzer technique. Variations in chlorite concentration over the last 0.5 Ma display a typical pattern of glacial–interglacial changes, with its bulk content in loess units approximately twice that in paleosol units. This climate-driven chlorite change is more pronounced in the fine-size fraction (5–20 μm) of the loess deposits. Evidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 56 publications
1
3
0
Order By: Relevance
“…The three‐stage MIS3 can also be envisaged on the SUS curve of our loess section (Figure 3). This type of subdivision for MIS3 was in accordance with the study of land snail faunal assemblages in the middle part of the Chinese Loess Plateau (e.g., Chen & Wu, 2008). In addition, the average δ 18 O value of C. pulveratrix was −5.3‰ during the MIS3 stage.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…The three‐stage MIS3 can also be envisaged on the SUS curve of our loess section (Figure 3). This type of subdivision for MIS3 was in accordance with the study of land snail faunal assemblages in the middle part of the Chinese Loess Plateau (e.g., Chen & Wu, 2008). In addition, the average δ 18 O value of C. pulveratrix was −5.3‰ during the MIS3 stage.…”
Section: Discussionsupporting
confidence: 84%
“…This assemblage change indicated that the climate was warmer and more humid at early MIS3 than at late MIS3. A faunal assemblage study of land snails in the central Chinese Loess Plateau also suggested that the temperature and humidity were higher during early MIS3 (Chen & Wu, 2008). However, the δ 18 O value of C. pulveratrix was highly variable during early MIS3 and was not as low as that during late MIS3 (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is susceptible to weathering and provides free Fe for secondary ferrimagnetic mineral formation (e.g., Spassov et al, 2003; Torrent et al, 2007; Peng et al, 2014). Therefore, magnetic mineral concentration through lessivage, removal of carbonates (Singer et al, 1996), and chlorite weathering (He et al, 2018; Hyodo et al, 2020; Ye et al, 2020) are likely in these Bt(b) horizons. This might explain why high χ lf and χ fd % are observed in the Bt(b) horizons of loess–paleosol sequences in northern Iran.…”
Section: Resultsmentioning
confidence: 99%